High‐resolution MRI of mummified tissues using advanced short‐T2 methodology and hardware. Issue 3 (3rd October 2020) - Baadsvik, Emily Louise; Weiger, Markus; Froidevaux, Romain; Rösler, Manuela Barbara; Brunner, David Otto; Öhrström, Lena; Rühli, Frank Jakobus; Eppenberger, Patrick; Pruessmann, Klaas Paul
Abstract : Purpose: Evolutionary medicine aims to study disease development from a long‐term perspective, and through the analysis of mummified tissue, timescales of several thousand years are unlocked. Due to the status of mummies as ancient relics, noninvasive techniques are preferable, and, currently, CT imaging is the most widespread method. However, CT images lack soft‐tissue contrast, making complementary MRI data desirable. Unfortunately, the dehydrated nature and short T2 times of mummified tissues render them practically invisible to standard MRI techniques. Specialized short‐T2 approaches have therefore been used, but currently suffer severe resolution limitations. The purpose of the present study is to improve resolution in MRI of mummified tissues. Methods: The zero‐TE‐based hybrid filling technique, together with a high‐performance magnetic field gradient, was used to image three ancient Egyptian mummified human body parts: a hand, a foot, and a head. A similar pairing has already been shown to increase resolution and image quality in MRI of short‐T2 tissues. Results: MRI images of yet unparalleled image quality were obtained for all samples, reaching isotropic resolutions of 0.6 mm and SNR values above 100. The same general features as present in CT images were depicted but with different contrast, particularly for regions containing embalming substances. Conclusion: Mummy MRI is a potentially valuable tool for (paleo)pathological studies, as well as for investigations into ancient mummification processes. The results presented here show sufficient improvement in the depiction of mummified tissues to clear new paths for the exploration of this field.